2008
DOI: 10.1089/jop.2007.0082
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Evaluation of the Ocular Distribution of 14C-Labeled Bromfenac Following Topical Instillation into the Eyes of New Zealand White Rabbits

Abstract: Significant penetration and measurable amounts of (14)C-bromfenac were detected in all ocular tissues over 24 h, including the sclera, choroid, and retina. These results strongly suggest the utility of bromfenac ophthalmic solution 0.09% in treating inflammation of both the anterior and posterior ocular segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 10 publications
2
34
0
7
Order By: Relevance
“…In rabbits, bromfenac was detected in the retina, choroid, and sclera 24 hours after topical instillation; therefore, it could be used to treat inflammation in the posterior pole. 19 Yoshinaga et al 20 recently showed that bromfenac inhibits CNV by decreasing VEGF expression through the antioxidant protein heme oxygenase 1-dependent pathway in an experimental rat model. Clinically, Grant 8 suggested a synergistic effect of topical bromfenac on anti-VEGF treatment in a nonrandomized, retrospective, 6-month study; patients with topical bromfenac had a significant improvement in visual outcomes and a significant decrease in the number of ranibizumab injections.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, bromfenac was detected in the retina, choroid, and sclera 24 hours after topical instillation; therefore, it could be used to treat inflammation in the posterior pole. 19 Yoshinaga et al 20 recently showed that bromfenac inhibits CNV by decreasing VEGF expression through the antioxidant protein heme oxygenase 1-dependent pathway in an experimental rat model. Clinically, Grant 8 suggested a synergistic effect of topical bromfenac on anti-VEGF treatment in a nonrandomized, retrospective, 6-month study; patients with topical bromfenac had a significant improvement in visual outcomes and a significant decrease in the number of ranibizumab injections.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Therefore, NSAID treatment is preferred, and these compounds are being extensively studied in patients and animal models to assess their toxicity, pharmacokinetics, neuroprotective properties, and anti-inflammatory and antiedema effects, among others. 4,[7][8][9][10][11][12][13][14][15][16] One such NSAID, bromfenac, is an inhibitor of the cyclooxygenase (COX) enzymes COX1 and COX2, and is more selective for COX2 than for COX1. 17 In rabbits, topical bromfenac reaches the vitreous and retinochoriodal tissues, and after a single topical administration is detectable in the retinochoroid up to 24 hours.…”
mentioning
confidence: 99%
“…17 In rabbits, topical bromfenac reaches the vitreous and retinochoriodal tissues, and after a single topical administration is detectable in the retinochoroid up to 24 hours. 8,17,18 Kida et al 19 showed that compared to nepafenac and diclofenac, bromfenac concentration after topical application on rabbit eyes was continuously higher in the retinochoroidal tissues. Thus, bromfenac may have a better therapeutic effect than these two other NSAIDs in retinochoroidal inflammatory diseases.…”
mentioning
confidence: 99%
“…Baklayan et al presented data from two separate but similar studies in which bromfenac and nepafenac were administered at three times the commercial dose in an animal model. 24 Bromfenac achieved measurable levels in all major ocular tissues that were detectable at 24 hours, but no significant levels of nepafenac/amfenac were detected in the aqueous humour and choroid after 12 hours and in the retina after six hours (see Figure 3). …”
Section: Penetration Of Ocular Tissuesmentioning
confidence: 98%
“…24,29 These early peak concentrations in aqueous humour remain above the concentration required to inhibit COX-2 by 50%…”
Section: Sustained Therapeutic Activitymentioning
confidence: 98%